Direct Isomaltulose Synthesis From Beet Molasses by Immobilized Sucrose Isomerase - Wang, Qin-Qing; Yang, Ming; Hao, Jian-Hua; Ma, Zai-Chao (Frontiers in Bioengineering and Biotechnology, 2021)
Isomaltulose is becoming a focus as a functional sweetener for sucrose substitutes; however, isomaltulose production using sucrose as the substrate is not economical. Low-cost feedstocks are needed for their production. In this study, beet molasses (BM) was introduced as the substrate to produce isomaltulose for the first time. Immobilized sucrose isomerase (SIase) was proved as the most efficient biocatalyst for isomaltulose synthesis from sulfuric acid (H2SO4) pretreated BM followed by centrifugation for the removal of insoluble matters and reducing viscosity. The effect of different factors on isomaltulose production is investigated. The isomaltulose still achieved a high concentration of 446.4 ± 5.5 g/L (purity of 85.8%) with a yield of 0.94 ± 0.02 g/g under the best conditions (800 g/L pretreated BM, 15 U immobilized SIase/g dosage, 40°C, pH of 5.5, and 10 h) in the eighth batch. Immobilized SIase used in repeated batch reaction showed good reusability to convert pretreated BM into isomaltulose since the sucrose conversion rate remained 97.5% in the same batch and even above 94% after 11 batches. Significant cost reduction of feedstock costs was also confirmed by economic analysis. The findings indicated that this two-step process to produce isomaltulose using low-cost BM and immobilized SIase is feasible. This process has the potential to be effective and promising for industrial production and application of isomaltulose as a functional sweetener for sucrose substitute.